Russia-Ukraine Geopolitical Crisis Indirect Effects on Indonesia's Financial System Stability - Taqiyah, Baroktut; Didi Nuryadin (Jurnal Ekonomi Pembangunan, 2024)
The Russia-Ukraine geopolitical crisis that has occurred since February 2022 is known to have resulted in a surge in food and energy prices at the global level. The escalation of the situation has expanded to cause the Fed to respond by raising the benchmark interest rate. The interest rate hike is caused by high inflation, which reduces the purchasing power of the domestic community. Financial system stability in Indonesia is essential, considering that US monetary policy is still the mecca of the country's economy. In addition, the dollar currency is still the primary means of payment in international trade. This study was conducted to analyze whether this geopolitical crisis indirectly influences Indonesia's financial system stability. The research method used to examine is the Error Correction Model (ECM). The study results show that the interest rates of the US, JCI, Money Supply, and government bonds significantly affect the short and long term. Meanwhile, inflation variables only have a significant effect in the long term. This research has policy implications where synergy resilience is needed to maintain proactive and holistic risk management in systemic. It also evaluates potential dangers and develops methods to reduce NPL to maintain stability and sustainability during changes in change and interactions between institutions included in the Financial System Stability Committee.